The Effect of GEN-NIK (Marriage-Ready Generation) E-Comic-Based Educational Media on University Students’ Perceptions of Marriage in Banyumas - Maya Ulfiyah; Inggar Ratna Kusuma (Darul Yasin Al Sys, 2026)
The growing “marriage is scary” phenomenon in digital media has contributed to negative perceptions of marriage among university students, highlighting the need for engaging and contextual educational media that foster a more balanced understanding of marriage. This study aims to analyze the effect of GEN-NIK (Generasi Siap Nikah) e-comic-based marriage education on university students’ perceptions of marriage. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed. The study involved 147 unmarried university students aged 20–21 years, selected through purposive sampling from three higher education institutions in Banyumas. Data were collected using a marriage perception questionnaire adapted from the Marriage Perception Scale and analyzed using the Wilcoxon Signed Rank Test. The findings showed an increase in students’ positive perceptions of marriage after the intervention, as reflected in the rise of the mean perception score from 75.25 to 82.95. Statistical analysis revealed a significant effect, p < .001, with a large effect size, r = 0.79. These findings indicate that GEN-NIK e-comic-based marriage education significantly improves university students’ perceptions of marriage. The study contributes to marriage education and youth development by demonstrating the potential of digital comic-based media as a communicative, contextual, and engaging educational tool. Its practical implications emphasize the importance of developing accessible digital learning media to strengthen marriage literacy, reduce negative misconceptions about marriage, and support marriage preparedness among university students.